2021
DOI: 10.1177/13621688211057665
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teacher written feedback in EFL writing classrooms: Beliefs and practices in interaction

Abstract: As an important instructional affordance, teacher written feedback is widely used in second language (L2) writing contexts. While copious evidence has shown that such a pedagogical practice can facilitate L2 learners’ writing performance, especially their writing accuracy, little is known about how novice writing teachers conceptualize and enact written feedback in contexts of English as a foreign language (EFL). To fill this gap, we examined four novice writing teachers’ espoused written feedback beliefs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…As voiced by Annie, they learned how to write English texts primarily through a product-oriented approach, which accentuates the imitation of input and the accuracy of language forms. With the scarce experience in teaching writing and exploring the latest instructional methods like GBA, teacher-students in EFL secondary schools in China tend to be impacted by their learning experiences ( Cheng et al, 2021 ). They also valued the local issues like word choices, structure, and format highly in conceiving genre pedagogies and providing examples of GBWI practices, whereas giving less weight to global issues which systematically connected the discursive features of a certain text to its audience and rhetorical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…As voiced by Annie, they learned how to write English texts primarily through a product-oriented approach, which accentuates the imitation of input and the accuracy of language forms. With the scarce experience in teaching writing and exploring the latest instructional methods like GBA, teacher-students in EFL secondary schools in China tend to be impacted by their learning experiences ( Cheng et al, 2021 ). They also valued the local issues like word choices, structure, and format highly in conceiving genre pedagogies and providing examples of GBWI practices, whereas giving less weight to global issues which systematically connected the discursive features of a certain text to its audience and rhetorical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese saying, ‘being a teacher for only 1 day entitles one to lifelong respect from the student that befits his/her father’ (yiri weishi zhongshen weifu), expresses this hierarchical teacher-student relationship. Having been influenced by this culture throughout their own student life, Chinese EFL teachers are likely to develop firm beliefs regarding the teacher and student roles ( Cheng et al, 2021 ; Sun and Zhang, 2021 ; Zhang and Sun, 2022 ). As such, when conducting assessment, teachers tend to still take a dominant role in assessment and monitoring students’ learning despite their beliefs about the beneficial impact of student-involving assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The participants pointed out the instructor's feedback contained grammar corrections but focused more on the organization of arguments. Researchers found that Chinese teachers showed a stronger focus on correcting the use of grammar and vocabulary (Cheng et al, 2021). However, researchers tend to agree that the strategy and in uence of teacher feedback are context speci c.…”
Section: Feedback Focusmentioning
confidence: 99%